Peran Manajer dalam Mengelola Emosi Tim untuk Meningkatkan Kualitas Pelayanan pada WO Siharade Project - Julyansyah, Dwi; Renggani, Putri Dewi; Prayoga, Andyka Maulana; Damayanti, Mia; Nurasiah, Sofa Parihah (Teewan Journal Solutions, 2026)
This study aims to analyze the role of managers in managing team emotions to improve service quality at WO Siharade Project. The study employed a qualitative approach using a descriptive method. Data were collected through semi-structured interviews, observations, and documentation involving the manager and team members directly engaged in operational activities. Data were analyzed through the stages of data reduction, data display, and conclusion drawing, with triangulation techniques applied to ensure data validity. The findings indicate that managers play a significant role in enhancing service quality through five key aspects: identifying team members' emotional conditions at an early stage, regulating their own emotions as role models, fostering open communication that creates psychological safety, resolving conflicts objectively and in a solution-oriented manner, and maintaining the emotional stability of the team throughout the service process. Effective emotional management was found to improve work coordination, professionalism, responsiveness, and customer satisfaction. This study contributes to the development of organizational behavior literature, particularly regarding the application of emotional intelligence in the Wedding Organizer industry, which remains relatively underexplored